Escena magazine: Chilean exile and the academic culture - Valverde Morales, Marcelo (2020)
The present work has been undertaken as part of the academic project Voces y rostros del exilio chileno en Costa Rica (translated as Voices and faces of Chilean exile in Costa Rica) of the Institute of Latin American Studies (IDELA).  It comprises an analysis of the Chilean exile in Costa Rica and its role in the creation of the magazine Escena, published since 1979.  The investigation has developed an account of the exile of its founders, the intellectual networks that contributed to the magazine, the exile Chilean authors and the cultural-historical context of the magazine’s  constitution.  The results of the work obtained from interviews and bibliographic review, demonstrate the contribution to Costa Rican culture of a publishing initiative of permanent validity, which in 2019 entered 40 years of existence.